Urejanje podeželskega prostora za rekreacijske namene na primeru zgornjega povodja reke Soče - Golja, Aleš (Urbani izziv, 2008)
Based on the upper Soča River basin, the article deals with the problem of exploitation of valuable natural features for tourist and recreational purposes. The goal was to propose a model of recreational use of a selected section of the Soča River, to put forward a proposal of legal framework for managing the selected area and work out a management plan for recreational purposes; thus the most burdened area of the Soča River during summer months was chosen, i.e. a 9 km reach of the Soča (between Log Čezsoški and Trnovo ob Soči), and accordingly a feasible marketing proposal, control proposal and spatial planning proposal were given in order to reduce the negative effects on the environment. The chosen methodology combines knowledge and practice from different fields, having in mind that this kind of problem solving should be carried out in an interdisciplinary connection of expert knowledge. Our basic theoretical premise has been enivronmental protection with an objective to preserve space as a value everywhere and in all its forms. The purpose of environmental protection is to encourage and direct such spatial development that provides a long-term basis for human health, well-being and quality of life as well as maintaining biotic diversity. This enables us to connect space with all its parts and features, sport recreation and tourism, thus achieving quality of life of local inhabitants, well-being of guests, protection of the natural environment, economic development, creation of new work places and income.
Keywords: environmental protection; namembnost; podeželje; Posočje; prostorsko urejanje; recreation; rekreacija; rural area; Soča; tourism; turizem; varstvo okolja